As estratégias sociais e econômicas da agricultura familiar: o caso da cooperativa de fruticultores de Abaetetuba – Cofruta - PA - ABREU, Eliane dos Santos de (2021)
Family farming has been over the years seeking new socioeconomic strategies to reproduce, which led to the creation of new organizational forms such as cooperatives. The present work aims to analyze the social and economic strategies of family farming through the Abaetetuba Fruit Growers Cooperative in the state of Pará. The methodology used was bibliographic research and field research, carried out with the application of 21 semi-structured questionnaires to the members. Family farming through COFRUTA has developed nine socio-economic and cultural strategies for their support and well-being. Cooperativism is presented as an important instrument used in the strengthening of family farming, enabling the development of entities that seek the strengthening of the collective and the maintenance of the peasant through resistance to the inequalities and invisibilities generated by a capitalist society.